Effect of Isometric and Isotonic Exercise Program on Increased Strength of Quardriceps Muscles in Osteoarthritis Patients in Singgasana Rama Physiotherapy Clinic Blitar - Syahputra, Irwan; Nurwijayanti, Nurwijayanti (Journal for Quality in Public Health, 2021)
Background: Osteoarthritis is a disease of the joints that can cause disability and is progressive in the joints which cause changes in the water content, proteoglycin content, and collagen in the joints. One of the ways to improve functional ability in osteoarthritis cases is to use isotonic and isometric training exercise. Pain is a clinical symptom of knee osteoarthritis, limiting movement due to pain over time will cause rehabilitation problems such as impaired flexibility and stability, reduction of muscle mass (atrophy). Mild and moderate intensity quadriceps strength training is effective at achieving optimal muscle strength and function without causing significant muscle damage. Destination: The purpose of this study was to analyze the effect of isotonic and isometric exercises on muscle strength. Research methods: This study uses a pre-experimental research type using "One Group Pre - test and Post - Test". This research has carried out the first observation (pretest) so that researchers can test the changes that occur after the treatment, and the control group. Result: with the Wilcoxon signed rank test test the isometric and isotonic groups had p = 0.000 while the control group had a significance value of p = 1,000; and the 3 groups test has different values, namely: isotonic exercise has a value of 27.67; isometric; 28.60; and control 12.73. The conclusion that can be concluded that the value of isometric training has the highest value, namely 28.60 which means it is the most effective exercise to increase the value of Manual Muscle Testing. Conclusion: There is an effect of giving isometric and isotonic exercises in strengthening the quadriceps muscles.